2023
DOI: 10.1039/d3cc01358h
|View full text |Cite
|
Sign up to set email alerts
|

Unusual coordination mode for 1,3-diphosphete ligands towards a Cr–Cr quintuple bond complex

Abstract: The reaction of LCr5CrL (L = N2C25H29, 1) with the phosphaalkynes R-CΞP (R = tBu, Me, Ad) yields the neutral dimerisation compounds [L2Cr2(µ,η1:η1:η2:η2-P2C2R2)] (R = tBu (2), Me (3)) and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…1). 10 However, although side-on coordination of phosphaalkynes is expected once a metal–metal bond is present in a molecule, more complex coordination modes 11 or even the fragmentation 12 of these species have also been reported. For example, Butenschön et al observed the fragmentation of t BuCP in the reaction with a (ω-di- tert -butylphosphanyl)(ethylcyclopentadienyl)cobalt chloride complex when using a threefold excess at r.t. under reductive conditions, resulting in a product with a carbyne and a phosphide ligand E .…”
mentioning
confidence: 99%
“…1). 10 However, although side-on coordination of phosphaalkynes is expected once a metal–metal bond is present in a molecule, more complex coordination modes 11 or even the fragmentation 12 of these species have also been reported. For example, Butenschön et al observed the fragmentation of t BuCP in the reaction with a (ω-di- tert -butylphosphanyl)(ethylcyclopentadienyl)cobalt chloride complex when using a threefold excess at r.t. under reductive conditions, resulting in a product with a carbyne and a phosphide ligand E .…”
mentioning
confidence: 99%